(untitled) (Research, Society and Development, 2020)
The objective of this research was to investigate the use of anabolic steroids and dietary supplements by gym users in the municipality of Cuiabá-MT and thus to sensitize the gym users to improve the quality and lifestyle of this population. The sample universe was 50 people, the research was conducted in July and August 2019, the instrument used was a questionnaire, containing 20 multiple choice questions. Most of the students were between 24 and 35 years old, 16 were female and 34 were male, regarding schooling, most of the interviewees had completed or ongoing higher education. Most attend the gym from six months to a year and the most practiced physical activity is bodybuilding. Of the 50 interviewees, 33 use a dietary supplement, along with the diet. BCAA is the most widely used supplement, and the main objective is muscle mass gain. 34 students say they are satisfied with the use. Most students report investing up to R 150.00 per month in dietary supplements, when asked about the indication most reported having sought professional help, 13 students by medical indication/nutritionist and 14 by indication of physical educator, the main reason for use was: improvement in physical condition. Of the total sample 50 (9) has already made/makes the use of anabolic steroids, among the two users claim to have had side effects and most students claim to have knowledge of its effects.